MADURA WOMEN AND AGRICULTURAL CONFLICT (Study on Agricultural Land Area) - Junaidi, Sidqi (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2022)
Land as a source of life makes farmers struggle to get land rights. Land is a symbol of independence for farmers because from the land they will make their lives better economically, socially and culturally. Responding to various unfair policies, women are more critical and dare to express their opinions. Peasant women are actively involved in the peasant movement from time to time. This paper describes the role of women in land conflicts. The role of women farmers in the struggle for land tenure in agrarian conflicts cannot be underestimated. Gender bias in the throes of reclaiming in agrarian conflicts is relatively not found. Farmers, be they men or women, want to reclaim power over the land. Agricultural land area controlled by the government and white people (read: china) for the use of the aquaculture industry is not in the name of women or men, but farmers' land. The struggle for sovereignty over agrarian resources, the militancy of women exceeds that of men. The women's movement is actively involved in the peasant movement.